Oral Traditions in Dayak Ma'anyan Rituals: An Anthropological Study - Kadek Sukiada; Cindy Dwi Yanti (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
ABSTRACT The Dayak people have a long history of relying on oral traditions to pass on their knowledge, beliefs and customs from one generation to the next. The aim of this research is to determine and inform the form and function of the Dayak Ma'anyan oral tradition, so that this tradition can be used as a reference for the Dayak community in Central Kalimantan. This research uses a descriptive qualitative methodology that describes the uniqueness of the oral traditions of the Dayak Ma'anyan tribe by looking at form and function as an analytical tool. The findings of this research show that in the oral tradition of the Dayak Manyan tribe's medical practices, basically in curing or dealing with a particular disease, tabit or lasang is generally treated, not only the biological aspects of the patient, but also the socio-cultural and spiritual aspects. Likewise, the oral tradition in the singing of Tinga Janyawai and Laisomena; Kuriding music as a traditional musical instrument typical of the Bakumpai Dayak tribe of Kalimantan and Dayak Ma'nyaan dances such as the dadas dance and other dances. Meanwhile, rituals in Maanyan Dayak society are associated with magical acts and the cult of ancestors as religious acts. Keywords: Implementation, Oral Tradition, Dayak Ma'anyan Ritual, and Anthropological Studies